2020
DOI: 10.3345/cep.2019.01438
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic and treatment guidelines for undescended testis

Abstract: Cryptorchidism or undescended testis is the single most com mon genitourinary disease in male neonates. In most cases, the testes will descend spontaneously by 3 months of age. If the testes do not descend by 6 months of age, the probability of spontaneous descent thereafter is low. About 1%-2% of boys older than 6 months have undescended testes after their early postnatal descent. In some cases, a testis vanishes in the abdomen or reascends after birth which was present in the scrotum at birth. An inguinal un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 65 publications
(84 reference statements)
0
40
0
7
Order By: Relevance
“…In the present study, we not only reported sperm retrieval rate and risk factors for unsuccessful sperm extraction, but also predictors for successful pregnancy in the female partners of males who had spermatozoa on mTESE. Our limitations include some points: Cryptorchidism is an important risk factors for GCNIS and has also threefold increased risk of testicular cancer later in life, compared to general population 20‐22 . A piece of testicular tissue was taken for only histopathologic examination to evaluate stages of spermatogenesis in the absence of mature spermatozoa on mTESE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we not only reported sperm retrieval rate and risk factors for unsuccessful sperm extraction, but also predictors for successful pregnancy in the female partners of males who had spermatozoa on mTESE. Our limitations include some points: Cryptorchidism is an important risk factors for GCNIS and has also threefold increased risk of testicular cancer later in life, compared to general population 20‐22 . A piece of testicular tissue was taken for only histopathologic examination to evaluate stages of spermatogenesis in the absence of mature spermatozoa on mTESE.…”
Section: Discussionmentioning
confidence: 99%
“…Our limitations include some points: Cryptorchidism is an important risk factors for GCNIS and has also threefold increased risk of testicular cancer later in life, compared to general population. [20][21][22] A piece of testicular tissue was taken for only histopathologic examination to evaluate stages of spermatogenesis in the absence of mature spermatozoa on mTESE.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Thus, orchiopexy is recommended between 6 and 18 months at the latest based on international guidelines. In conclusion, this review by Shin and Jeon 10) describes the importance of a timely referral and indications for referral to a surgical specialist for UDT. However, it would be better if Shin and Jeon 10) mentioned Korean data about UDT in this review.…”
mentioning
confidence: 97%
“…This article describes the diagnosis, differential diagnosis, hormone therapy, fertility, risk of testicular cancer, and timing of surgical therapy of UDT based on international guidelines. Shin and Jeon 10) suggest timely referral to a surgical specialist and timely surgical correction of UDT to improve fertility and decrease the risk of malignancy. Primary caregivers including general pediatricians should consider the following indications for referral: (1) the testis has not descended into the scrotum by 6 months of age, (2) newly diagnosed UDT after 6 months of age, or (3) suspected testicular torsion.…”
mentioning
confidence: 99%
See 1 more Smart Citation